2011
DOI: 10.1016/j.juro.2011.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Testicular Torsion: Demographics of National Orchiopexy Versus Orchiectomy Rates

Abstract: Nationally an average of 32% of the 411 pediatric torsion cases explored annually result in orchiectomy. Identified factors increasing the orchiectomy risk included age 1 to 9 years, black race and lack of private insurance. Efforts should continue to identify modifiable variables that can increase testicular salvage in patients with testicular torsion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
86
5
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 17 publications
4
86
5
4
Order By: Relevance
“…Shukla et al were the first authors to hypothesize an association between cold weather and testicular torsion in 1982 (3). Since than, a total of 9 studies have found a positive association between low ambient temperature and testicular torsion (3-11) whereas 4 did not (12)(13)(14)(15). All studies that found a positive association were conduced in cold regions or regions with high temperature amplitude.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shukla et al were the first authors to hypothesize an association between cold weather and testicular torsion in 1982 (3). Since than, a total of 9 studies have found a positive association between low ambient temperature and testicular torsion (3-11) whereas 4 did not (12)(13)(14)(15). All studies that found a positive association were conduced in cold regions or regions with high temperature amplitude.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are four studies that have not observed seasonal variation of testicular torsion. In a series of 2,876 men, Cost et al have not observed seasonal variations of testicular torsion (15). However, this study included men from all across the United States, a country with very different weather conditions, without distinctions according to regions' temperature (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although much is known about TT, recent reviews have identified remaining controversies [3,4]. For instance, some research has indicated that Caucasian patients have a greater chance of having the testicle salvaged than minorities [5], but other studies have reported no difference between groups [6]. Patients who underwent orchiectomies have been shown to be older in some [5,6] but not all [2] studies.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] However, Cost et al 17 Brazil reported an increase in the occurrence of torsion during the winter, 18 but it included patients with testicular torsion presumed on admission, thus making it difficult to establish precise conclusions, because only 16% to 42% of boys with acute scrotal pain have surgically confirmed testicular torsion. [19][20][21] Hypothesizing that cold weather is the main initiating event for acute testicular torsion would be too simplistic.…”
mentioning
confidence: 99%